Evaluation of the tapered PMMA fiber sensor response due to the ionic interaction within electrolytic solutions - Batumalay, M.; Rahman, H.A.; Kam, W.; Ong, Y.S.; Ahmad, F.; Zakaria, Rozalina; Harun, Sulaiman Wadi; Ahmad, Harith (Taylor & Francis, 2014)
A tapered plastic multimode fiber (PMMA) optical sensor is proposed and demonstrated for continuous monitoring of solutions based on different concentration of sodium chloride and glucose in deionized water The tapered PMMA fiber was fabricated using an etching method involving deionized water and acetone to achieve a waist diameter and length of 0.45 mm and 10 mm, respectively, and was used to investigate the effect of straight, U-shape, and knot shape against concentration for both sodium chloride and glucose. The results show that there is a strong dependence of the electrolytic and non-electrolytic nature of the chemical solutions on the sensor output. It is found that the sensitivity of the sodium chloride concentration sensor with the straight tapered fiber probe was 0.0023 mV/%, which was better than the other probe arrangements of U-shape and knot. Meanwhile, the glucose sensor performs with the highest sensitivity of 0.0026 mV/wt % with the knot-shaped tapered fiber probe. In addition, a tapered PMMA probe which was coated by silver film was fabricated and demonstrated using calcium hypochlorite (G70) solution. The working mechanism of such a device is based on the observed increment in the transmission of the sensor that is immersed in solutions of higher concentration. As the concentration varies from 0 ppm to 6 ppm, the output voltage of the sensor increases linearly from 3.61 mV to 4.28 mV with a sensitivity of 0.1154 mV/ppm and a linearity of more than 99.47%. The silver film coating increases the sensitivity of the proposed sensor due to the effective cladding refractive index, which increases with the coating and thus allows more light to be transmitted from the tapered fiber.